Treatment landscape of advanced breast cancer patients with hormone receptor positive HER2 negative tumors – Data from the German PRAEGNANT breast cancer registry. (February 2018) - Hartkopf, Andreas D.; Huober, Jens; Volz, Bernhard; Nabieva, Naiba; Taran, Florin-Andrei; Schwitulla, Judith; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; et al.
Abstract: Purpose: This study describes comprehensive data from a breast cancer registry concerning the use of endocrine treatment (ET) and chemotherapy in the first, second and higher therapy lines in hormone receptor (HR) positive, HER2 negative metastatic breast cancer (MBC). Methods: The PRAEGNANT study is a real-time registry for patients with MBC. Therapies were categorized into the following categories: chemotherapy, aromatase inhibitor (AI), tamoxifen, fulvestrant, or everolimus plus ET and reported for first, second and third line or higher therapy use. Also treatment sequences for the first, second and third therapy line were analyzed. Results: This analysis includes 958 patients with HR positive, HER2 negative MBC. 42.7% were treated with a chemotherapy in the first therapy line compared to 45.9% receiving an ET. A total of 25.9% were treated with everolimus plus anti-hormone therapy in any therapy line. 34.1% were treated with fulvestrant as single agent therapy. Analyzing therapy sequences, the administration of three different chemotherapies in a row was the most frequently used pattern. Conclusions: This analysis shows that across all three first therapy lines chemotherapy is a dominant therapy for HR positive, HER2 negative MBC patients. Education about the efficacy of ET might help to increase its use and decrease the possible burden of chemotherapy related toxicities. Highlights: Aromatase inhibitors are used predominantly in HR-/HER2-metastatic breast cancer patients. First-line chemotherapy was used in 42% of HR-/HER2-metastatic breast cancer patients. The sequence of chemotherapy.→chemotherapy→chemotherapy was most frequently used A quarter of all HR+/HER2-metastatic breast cancer patients are treated with everolimus.